Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a ) \(\left(\frac{2}{5}-x\right):1\frac{1}{3}+\frac{1}{2}=-4\)
\(\left(\frac{2}{5}-x\right):\frac{4}{3}+\frac{1}{2}=-4\)
\(\left(\frac{2}{5}-x\right):\frac{4}{3}=-4-\frac{1}{2}\)
\(\left(\frac{2}{5}-x\right):\frac{4}{3}=-\frac{9}{2}\)
\(\frac{2}{5}-x=-\frac{9}{2}.\frac{4}{3}\)
\(\frac{2}{5}-x=-3\)
\(x=\frac{2}{5}-\left(-3\right)\)
\(x=\frac{2}{5}+3\)
\(x=\frac{3}{5}-\frac{15}{5}\)
\(x=-\frac{12}{5}\)
Vay \(x=-\frac{12}{5}\)
b ) \(\left(-3+\frac{3}{x}-\frac{1}{3}\right):\left(1+\frac{2}{5}+\frac{2}{3}\right)=-\frac{5}{4}\)
\(\left(-3+\frac{3}{x}-\frac{1}{3}\right):\left(\frac{15}{15}+\frac{6}{15}+\frac{10}{15}\right)=-\frac{5}{4}\)
\(\left(-3+\frac{3}{x}-\frac{1}{3}\right):\left(\frac{15+6+10}{15}\right)=-\frac{5}{4}\)
\(\left(-3+\frac{3}{x}-\frac{1}{3}\right):\frac{31}{15}=-\frac{5}{4}\)
\(\left(-3+\frac{3}{x}-\frac{1}{3}\right)=-\frac{5}{4}.\frac{31}{15}\)
\(\left(-3+\frac{3}{x}-\frac{1}{3}\right)=-\frac{1}{4}.\frac{31}{3}\)
\(-3+\frac{3}{x}-\frac{1}{3}=-\frac{31}{12}\)
\(-3+\frac{3}{x}=-\frac{31}{12}+\frac{1}{2}\)
\(-3+\frac{3}{x}=-\frac{31}{12}+\frac{6}{12}\)
\(-3+\frac{3}{x}=\frac{-25}{12}\)
\(\frac{3}{x}=\frac{-25}{12}+3\)
\(\frac{3}{x}=\frac{-25}{12}+\frac{36}{12}\)
\(\frac{3}{x}=\frac{5}{6}\)
\(\frac{18}{6x}=\frac{5x}{6x}\)
Đèn dây , bạn tự làm tiếp nhé , de rồi chứ
1.
a) \(x\in\left\{4;5;6;7;8;9;10;11;12;13\right\}\)
b) x=0
d) \(x=\frac{-1}{35}\) hoặc \(x=\frac{-13}{35}\)
e) \(x=\frac{2}{3}\)
a)\(\left|x+\frac{1}{4}\right|-\frac{3}{4}=5\%\)
\(\left|x+\frac{1}{4}\right|=\frac{1}{20}+\frac{3}{4}\)
\(\left|x+\frac{1}{4}\right|=\frac{4}{5}\)
\(\Rightarrow x+\frac{1}{4}=\pm\frac{4}{5}\)
*\(x+\frac{1}{4}=\frac{4}{5}\) *\(x+\frac{1}{4}=-\frac{4}{5}\)
\(x=\frac{4}{5}-\frac{1}{4}\) \(x=-\frac{4}{5}-\frac{1}{4}\)
\(x=\frac{11}{20}\) \(x=-\frac{21}{20}\)
\(\frac{2}{3}+2\left(x-1\right)=\frac{4}{5}\)
=> \(2\left(x-1\right)=\frac{4}{5}-\frac{2}{3}\)
=> \(2\left(x-1\right)=\frac{2}{15}\)
=> \(x-1=\frac{1}{15}\)
=> \(x=\frac{16}{15}\)
2/3+2(x+1)=4/5
2(x+1)=4/5-2/3
2(x+1)=2/15
(x+1)=2/15:2
(x+1)=1/15
x=1/15-1
x=-14/15
vậy x=-14/15